Correction to: Multifactorial pathways in burn injury-induced chronic pain: novel targets and their pharmacological modulation (Molecular Biology Reports, (2022), 49, 12, (12121-12132), 10.1007/s11033-022-07748-9) - Roy T.K.; Uniyal A.; Akhilesh; Tiwari V. (My University, 2025)
In the original publication of the article, the third author name is corrected from “Akhilesh.” to “Akhilesh”. The original article has been corrected. © 2023, Springer Nature B.V.